Association between Connective Tissue Dysplasia and the Pregnancy Progress and Outcomes - Torres I. Moore; Bennett I. Martin (Academic Journal of Clinicians, 2025)
A priority area of modern medicine is improving the protection of mothers and children. Scientific research conducted in obstetrics and perinatology requires comprehensive development. Studying the influence of extragenital pathology in women on the course of pregnancy and childbirth, on the development of the fetus and newborn, their adaptive capabilities, morbidity and mortality remains important. Congenital systemic diseases of connective tissue, defined in the literature as "connective tissue dysplasia" (CTD) are currently experiencing increased interest from researchers. This is due, first of all, to progress in studying the basis for the development of this pathology, secondly, to the detailed elaboration of the main clinical manifestations of CTD. Currently, modern laboratory and instrumental studies facilitate the diagnosis of existing maternal and fetal diseases in most cases, but, as a rule, they do not allow for a timely determination of the likelihood of developing a particular pathological condition before the onset of clinical symptoms. We believe it is advisable to conduct a clinical examination of pregnant women and their newborns, as well as a morphological study of the placenta, umbilical cord, and fetal membranes of mothers in childbirth. This will allow for the timely initiation of comprehensive, pathogenetically based therapy, thereby reducing maternal and perinatal morbidity and mortality. The aim of the study is to develop a comprehensive program of step-by-step tactics for managing pregnant women with various types of connective tissue dysplasia by improving the principles of their medical examination.